The Impact of the Long-Term Kampus Mengajar Program on the Development of Student’s Soft Skills and Hard Skills - Selvia Aprilita; Berta Apriza (LPPM Undiksha, 2025)
The Kampus Mengajar Program aims to improve the quality of basic education by involving students as teacher assistants in schools. In addition to impacting schools, this program contributes to developing students' soft and hard skills. This study aims to explore the long-term impact of the Kampus Mengajar Program on the development of students' soft and hard skills. This study uses the Systematic Literature Review (SLR) method by reviewing 10 articles from accredited journals, such as the Al-Ishlah Education Journal, the Indonesian Action Research Journal (JRTI), the Journal of Education Research, and the Wahana Pendidikan Scientific Journal. This study focuses on analysing the program's long-term impact on students' work readiness after graduation. The results of the study indicate that this program improves communication, leadership, teamwork, and problem-solving skills. In addition, students acquire technical skills such as lesson planning, technology utilization, and effective teaching strategies. This program helps students bridge the gap between theory and practice, increasing graduates' competitiveness in the workplace. This study provides insights into the effectiveness of experiential learning and its implications for higher education policy in Indonesia to prepare graduates who are more competitive, adaptive, and ready to face workplace challenges.